Effect of Rare Earth Ions on the Properties of Composites Composed of Ethylene Vinyl Acetate Copolymer and Layered Double Hydroxides - Wang, Lili; Li, Bin; Zhao, Xiaohong; Chen, Chunxia; Cao, Jingjing (PLOS ONE, 2012)
Background The study on the rare earth (RE)-doped layered double hydroxides (LDHs) has received considerable attention due to their potential applications in catalysts. However, the use of RE-doped LDHs as polymer halogen-free flame retardants was seldom investigated. Furthermore, the effect of rare earth elements on the hydrophobicity of LDHs materials and the compatibility of LDHs/polymer composite has seldom been reported. Methodology/Principal Findings The stearate sodium surface modified Ni-containing LDHs and RE-doped Ni-containing LDHs were rapidly synthesized by a coprecipitation method coupled with the microwave hydrothermal treatment. The influences of trace amounts of rare earth ions La, Ce and Nd on the amount of water molecules, the crystallinity, the morphology, the hydrophobicity of modified Ni-containing LDHs and the adsorption of modifier in the surface of LDHs were investigated by TGA, XRD, TEM, contact angle and IR, respectively. Moreover, the effects of the rare earth ions on the interfacial compatibility, the flame retardancy and the mechanical properties of ethylene vinyl acetate copolymer (EVA)/LDHs composites were also explored in detail. Conclusions/Significance S-Ni0.1MgAl-La displayed more uniform dispersion and better interfacial compatibility in EVA matrix compared with other LDHs. Furthermore, the S-Ni0.1MgAl-La/EVA composite showed the best fire retardancy and mechanical properties in all composites.